Sosialisasi Penerapan Bahan Ajar Berbasis Flash Cards Bagi Guru Bahasa Inggris MI Mambaul Ulum Banjarejo Pagelaran Malang - Mulis, Mulis (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2024)
This Community Service Activity aims to socialize the application of flashcard-based teaching materials for English teachers at MI Mambaul Ulum Banjarejo Pagelaran Malang. This activity was carried out on August 14 2023 at the Madrasah Ibdidaiyah Mambaul Ulum Banjarejo Pagelaran Malang office with socialization and training practices. The results of community service activities can improve teachers' abilities and skills in using or applying flashcard-based teaching materials in teaching and learning activities. This service received a positive response from the head of the madrasah and teachers who teach English.